Modulation of Inflammatory Markers by Vitamin D and Pioglitazone to Combat Renal Dysfunction in Type 2 Diabetic Rats - Maheshwari, Rajesh A. (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: This study is designed to assess the outcomes of Vitamin D (Vit D) and Pioglitazone (PIO) on metabolic control, kidney function, inflammatory markers, and histopathology in rats with streptozotocin-nicotinamideinduced diabetes. Materials and Methods: Rats were randomly assigned to five groups: Normal control, diabetic control (DC), Vit D-treated, PIO-treated, and combined Vit D + PIO-treated, with treatments administered orally for 8 weeks. Blood samples were analyzed for glucose, insulin, homeostasis model assessment of insulin resistance (HOMA-IR), blood urea nitrogen (BUN), creatinine, and inflammatory markers, and kidney tissues were assessed histopathologically after euthanasia. Results: Both Vit D and PIO treatments reduced glucose, insulin, and HOMA-IR levels, with the combined treatment showing the most significant improvements, suggesting a synergistic effect. Both Vit D and PIO also reduced serum creatinine and BUN levels, with the combination therapy leading to a more substantial reduction in creatinine, although no significant improvement in BUN was observed compared to Vit D alone. The combination therapy significantly reduced C-reactive protein, monocyte chemoattractant protein-1, and interleukin-6 levels compared to the DC, though no additional benefits were observed for tumor necrosis factor-alpha, cystatin-C, and transforming growth factor-beta 1. Histopathological analysis revealed mild degenerative changes in the DC group, while the combined Vit D + PIO treatment restored kidney structure to near normal, with minimal vascular congestion. Conclusion: Overall, both Vit D and PIO positively impacted glucose regulation, kidney function, and inflammatory markers in diabetic rats, with combination therapy showing superior efficacy, particularly in improving metabolic control and kidney histology.